Challenges in the Care of IBD Patients During the CoViD-19 Pandemic: Report From a "Red Zone" Area in Northern Italy. Issue 6 (21st April 2020) - Occhipinti, Vincenzo; Pastorelli, Luca
Abstract : Since February 20, 2020, in Italy, we have been confronting the dramatic challenge of the SARS-CoV-2 outbreak, which has completely overthrown our medical practice. We report our experience as an IBD center in Lombardia, the most affected region in Italy.